“Bivalent” regions of cytosine methylation and H3K27 acetylation suggest an active role for DNA methylation at enhancers - Charlet, Jessica (Mol Cell, 2016)
The role of cytosine methylation in the structure and function of enhancers is not well understood. In this study, we investigate the role of DNA methylation at enhancers by comparing the epigenomes of the HCT116 cell line and its highly demethylated derivative, DKO1. Unlike promoters, a portion of regular and “super-” or “stretch” enhancers show active H3K27ac marks co-existing with extensive DNA methylation, demonstrating the unexpected presence of “bivalent chromatin” in both cultured and uncultured cells. Furthermore, our findings also show that bivalent regions have fewer nucleosome-depleted regions and transcription factor binding sites than monovalent regions. Reduction of DNA methylation genetically or pharmacologically leads to a decrease of the H3K27ac mark. Thus DNA methylation plays an unexpected dual role at enhancer regions, being anti-correlated focally at transcription factor binding sites but positively correlated globally with the active H3K27ac mark to ensure structural enhancer integrity.